Application of ICT tools in teaching American English for computer science students in the context of global challenges - Symonenko, Svitlana; Симоненко, Світлана Вікторівна; Симоненко, Светлана Викторовна; Zaitseva, Natalia; Зайцева, Наталя Володимирівна; Зайцева, Наталья Владимировна; Vynohradova, Marharyta; Виноградова, Маргарита Сергіївна; Виноградова, Маргарита Сергеевна; Osadchyi, V. V.; Sushchenko, A. V. (My University, 2021)
The article deals with the urgent issue of American English learning for ITprofessionals under challenging conditions of the changeable economic situation in the world. Some statistical data on global education trends and its analysis are given to confirm the topicality of the problem. State-of-the-art trends in foreign language teaching in the context of global challenges are presented. It is stated that informal education environments, distant learning platforms, virtual reality environments, artificial intelligence applications and collaboration platforms are to be mastered by Ukrainian undergraduates. Certain peculiarities of choosing and studying British and American English course by students of IT-specialities at three Ukrainian universities are given: the course choice procedure, the reasons for course preference, and the syllabus content. The best technologies, applications and tools for classroom activities and independent learning are substantiated, specific examples of their application for British and American English course learning are presented. The transferability of the skills inculcated in the course participants through implementation of the certain tools is founded.
Keywords: ITprofessionals; foreign languages; American English